Analysis of the Wet Noodles Quality Produced From the Purple Sweet Potato Flour - Sartika, Ikramina; Holinesti, Rahmi; Insan, Ranggi Rahimul (Universitas Negeri Padang, 2022)
The use of purple sweet potato in West Sumatra is still limited to a few types of food products. In support of the government's program, namely the Food Security Program, the diversification of processed products based on local ingredients, one of which is purple sweet potato. Purple sweet potato has the potential to be used as a functional food ingredient to make flour because it contains carbohydrates, protein, vitamins, β-carotene and, anthocyanins needed by the body and can act as natural dyes in the food industry as well as a source of antioxidants that can play a role in fighting free radicals. . The focus of this research is to utilize the potential of purple sweet potato flour in processing wet noodles as a natural dye. Noodles are one of the ready-to-eat food products and alternative foods to replace staple foods, the price is cheap, the taste is good, and the practical processing is the main factor for many people who like noodles. This study aims to analyze the wet noodles produced from purple sweet potato flour, the observed qualities include color, aroma, texture and, taste. The percentage ratio of purple sweet potato flour used was 0%, 15%, 30%, and 45%. This type of research is a pure experiment using a completely randomized design (CRD) method with four treatments and three repetitions. Data collection techniques were carried out by distributing organoleptic formats to 5 expert panelists. Data were analyzed using ANOVA if Fcount Ftable then continued with Duncan's test. The results showed that there was a significant effect on the quality of color, texture, and taste of wet noodles produced from purple sweet potato flour. The best treatment of purple sweet potato flour substitution on the quality of wet noodles was in treatment (X1) as much as 15%